The Association between Obesity and the Risk of Cesarean Delivery and other Adverse Pregnancy Outcomes in Singleton Term Pregnancies - Korapin Rudtanasudjatum; Teerapat Chullapram (The Royal Thai College of Obstetricians and Gynaecologists, 2008)
ObjectiveTo compare the risk of cesarean delivery as well as antenatal complications, complications during delivery and neonatal outcomes between pregnant women with pre-pregnancy obesity versus normal pre-pregnancy body mass index (BMI). Study design Cohort study. Materials and Methods The population studied included pregnant women with singleton pregnancies of gestational age 37 completed weeks or more who were admitted to labor room, Chonburi Hospital, from May 1, 2006 to April 30, 2007. All pregnant women with pre-pregnancy BMI 25 kg/m2 or over were enrolled. The control group included the pregnant women who were admitted to the labor room next to each studied case and had pre-pregnancy BMI 18.5-22.9 kg/m2. Patients with previous cesarean delivery, private case and undelivered were excluded. Cesarean delivery rates as well as maternal and neonatal outcomes were compared. ResultsSix-hundred and forty six patients were enrolled, 323 patients in each group. Cesarean delivery was significantly higher in obese women (RR 2.3, 95% CI 1.63-3.14). The risk of cesarean delivery was increased with increasing BMI (RR 2.2 in BMI 25-29.9 kg/m2and 2.9 in BMI ≥30 kg/m2). Cesarean delivery due to cephalopelvic disproportion was significantly higher in the obese group (18% VS 8%, RR 2.23, 95% CI 1.4-3.5). Moreover, cesarean delivery due to preeclampsia in the obese group was 14-fold. Obese women had a relative risk of 5.0 (95% CI 2.3-11.1) for pregnancy-induced hypertension and 2.3 (95% CI 1.5-3.5) for large for gestational age (LGA). No significant differences were found between obesity and the risk of gestational diabetes, placenta previa, abruptio placentae, abnormal presentation, forceps extraction, shoulder dystocia, 3rd or 4th degree perineal tear, small for gestational age (SGA), macrosomia as well as low apgar score. Conclusion Pre-pregnancy obesity is strongly associated with the risk of cesarean delivery as well as other pregnancy complications and perinatal conditions.